Documentary, world history, and national power in the PRC : global rise in Chinese eyes - Müller, Gotelind (Abingdon, Oxon ; New York : Routledge, 2013)
"Documentaries have recently become a favourite format for Chinese state-directed media to present an officially sanctioned view of history. Indeed, this is not confined to Chinese national history. In stark contrast to the earlier self-centred preoccupation with Chinese history, there has been an upsurge in interest in foreign history, with a view to illuminating China's role not only in world history, but also on the global stage today, and in the future. This book examines three recent Chinese documentary television series which present the officially sanctioned view of the rise of the modern West, the reasons for the end of the Soviet Union, and the legitimisation of the present-day Chinese government via a specific reading of modern Chinese history to argue for a "Chinese rise" in the future. With a focus on these documentaries, Gotelind Müller discusses how history is presented on screen, and explores the function of visual history for memory culture and wider society. Further, this book reveals how the presentation of Chinese and foreign history in a global framework impacts on the officially transmitted views on Self and Other, and thus provides a keen insight into how the Chinese themselves regard their "global rise". Documentary, World History, and National Power in the PRC will be welcomed by students and scholars working across a number of fields, including Chinese studies, East Asian studies, media studies, television studies, history and memory studies. "--
Introduction -- Foreign models for the public: the TV documentary Daguo jueqi (The Rise of the Great Powers) -- China's potentials on display: the sequel documentary Fuxing zhi lu (Road to Revival) -- Soviet failure lessons for insiders: the party-educational documentary Ju an si wei (Alert to Danger while Dwelling in Safety) -- Framing visions of China and the world: the state, documentary, and history in comparative perspective.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Documentary television programs -- China -- History and criticism; Historical television programs -- China -- History and criticism; Television and history -- China; History on television; Electronic books